Comparative study on the predictive value of TyG, TyG-BMI, and TG/HDL-C for progression-free survival in patients with locally advanced nasopharyngeal carcinoma - Xiao, Zhehao; Liang, Zhuowei; Chen, Weiling; Huang, Hejing; Qu, Song (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to explore the relationship between the triglyceride glucose (TyG) index, triglyceride glucose-body mass index (TyG-BMI), and triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-C) of locally advanced nasopharyngeal carcinoma (LA-NPC) and progression-free survival (PFS) to investigate their potential as prognostic indicators.MethodsThis research involved a retrospective analysis of data pertaining to patients with LA-NPC from the Guangxi Medical University Cancer Hospital. The analysis categorized patients into a progression group and a control group according to their disease control status. The correlation of three indicators with PFS was established utilizing the Cox proportional hazards model, Kaplan–Meier (K-M) analysis, and restricted cubic spline (RCS) analysis. Three predictive models were developed based on the three indicators, and their predictive ability was assessed.ResultsTyG, TyG-BMI, and TG/HDL-C are independent predictors of PFS in LA-NPC patients, and all exhibit a non-linear relationship. Patients in the high TyG, TyG-BMI, and TG/HDL-C groups have significantly lower PFS compared to those in the low groups, and this effect persists after adjusting for confounding factors. A multivariate analysis confirmed that lactate dehydrogenase (LDH) and EBV_DNA are also independent prognostic factors for PFS. The models that utilize these indicators outperform traditional tumor node metastasis (TNM) staging, with the TyG-based model demonstrating the strongest predictive ability for PFS.ConclusionTyG, TyG-BMI, and TG/HDL-C are potential prognostic biomarkers for the evaluation of PFS in individuals diagnosed with LA-NPC. Our research underscores the potential of these three indices to be utilized to enhance prognostic assessment and customize treatment strategies in the management of LA-NPC.